Determination of fouling mechanisms in enzymatic membrane reactor (EMR) for cyclodextrins production based on Resistance-In Series Model - A. M., Mimi Sakinah; Ismail, Ahmad Fauzi; Md. Illias, Rosli; Hassan, Osman (2005)
This study investigated the fouling mechanisms in ultrafiltration membrane during separation of cyclodextrins from starch and CGTase. The Resistance-In-Series Model was used to identify the responsible hydraulic resistances. The result showed that the weak adsorption fouling resistance (ra1) was the main factor that contributed the rate and extent of flux decline. Moreover the significant organic fouling that is contributed by starch, CDs, CGTase and intermediate by-products in organic colloids and/or macromolecular revealed that the fouling potential was ra1>rg>rcp>ra2. The overall results indicate that the fouling mechanisms may consist of pore mouth adsorption and subsequently narrowing of the pores as those components (starch and CGTase) are small enough not to be excluded by steric considerations. In the latter stage unreacted starch would be accumulated to form gel/cake layer. The measured flux recovery of enzymatic membrane reactor for CDs production was about 95%.